2010
DOI: 10.1111/j.1365-2567.2010.03348.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside-exposed dendritic cells inhibit T-cell effector function by promoting regulatory cell activity

Abstract: Summary Tumour pathogenesis is characterized by an immunosuppressive microenvironment that limits the development of effective tumour‐specific immune responses. This is in part the result of tumour‐dependent recruitment and activation of regulatory cells, such as myeloid‐derived suppressor cells and regulatory T cells in the tumour microenvironment and draining lymph nodes. Shedding of gangliosides by tumour cells has immunomodulatory properties, suggesting that gangliosides may be a critical factor in initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
0
18
0
Order By: Relevance
“… 23 , 485 The complete balance sheet for sphingolipids additionally includes uptake of sphingolipids from exogenous sources (such as albumin and lipoproteins) 486 , 487 and losses by efflux,( 488 ) lipoprotein secretion, 354 , 489 and shedding of membrane vesicles containing sphingolipids. ( 490 )…”
Section: Sphingolipid Metabolic Pathwaysmentioning
confidence: 99%
“… 23 , 485 The complete balance sheet for sphingolipids additionally includes uptake of sphingolipids from exogenous sources (such as albumin and lipoproteins) 486 , 487 and losses by efflux,( 488 ) lipoprotein secretion, 354 , 489 and shedding of membrane vesicles containing sphingolipids. ( 490 )…”
Section: Sphingolipid Metabolic Pathwaysmentioning
confidence: 99%
“…Dr. Stephan Ladisch described the capacity of lipid-raft associated ganglosides, which can be shed by tumors, to suppress immune function and promote tumor growth [4]. Tumors deficient in GM3/GM2 synthase impaired tumor growth and were associated with decreased MDSCs and increase in CD8+ T cells and NK cells.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…Besides its effects on cytotoxic T cells, tumor-derived sialoglycans are also able to dampen DC functions ( 96 100 ). Studies have shown that tumor-derived sialogangliosides inhibit the upregulation of co-stimulatory molecules (CD80/CD86) as well as IL-12 production by DCs, thus impairing T cell effector lymphocyte activation ( 101 ). This immunosuppressive effect is thought to be elicited by the interaction of highly sialylated tumor antigens with the siglec receptors expressed by DCs ( 102 , 103 ).…”
Section: Tumor-associated Glycan Determinants Subvert Key Immunologicmentioning
confidence: 99%